Transfert et utilisation des résultats en milieu de travail : le cas de la recherche sur les éboueurs au Québec - Madeleine Bourdouxhe; Laurent Gratton (Perspectives Interdisciplinaires sur le Travail et la Santé)
A study of mechanisms supporting the use of research results by workers and managers revealed the existence of certain conditions that are essential to the transmission process. This paper summarizes these conditions and presents a brief review of the principal approaches underlying knowledge transfer activities. The approach selected by the research team is illustrated by means of an example involving the transfer and use of research results relating to the occupational risks of domestic waste collection in Quebec. In this case, the conditions favorable to the transfer were met, namely involvement of future users in the design of the research protocol, rigorous scientific evaluation of the study, targeting of relevant partners, interpersonal contacts between these partners and the researchers, researchers’ involvement in transfer activities, and dissemination of results and recommendations using tools accessible to a broad range of users. However, the potential for transfer was limited by certain technological, economic and political considerations.